Numerical Study of the Mixing Co-Axial Jets - Neves, Fernando M. S. P. (2011)
This paper presents a numerical study of the effect of the turbulence intensity in the turbulent mixing of coaxial confined jets. The objective of this work is to study the effect of the initial levels of turbulence of each coaxial jet in the process of turbulent mixing for diameter ratios less than 2, which is the case of very low bypass turbofan engines. The computational method was tested using the available experimental data, and revealed good capabilities for the simulation of this kind of flows. The effect of the velocity ratio of the two streams is presented for velocity ratios of the two streams of 0.3, 1.5, and 6, and turbulence intensity ratios between 10 -5 and 10 5. The results revealed that for relatively high turbulence intensities of the outer jet a vortex is always present for velocity ratios of 6 or larger, and this is independent of the turbulence intensity ratio. When the turbulence intensity of the inner jet is kept constant and the ratio of turbulence intensities is increased, the recirculation zone decreases in size, its center moves further upstream until it disappears completely. The existence of a favorable pressure gradient as a similar effect, revealing that this is an additional parameter to be taken into consideration together with the velocity ratio and turbulence intensity ratio as far as the recirculation zone is concerned.